Recommendation for Scrum-Based Software Development Process with Scrum at Scale: A Case Study of Software House XYZ - Ahmad Jalaluddin; Eko K. Budiardjo; Kodrat Mahatma (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2024)
Software House XYZ employs Scrum as one of its software development processes. However, the company faces several challenges in the implementation of Scrum, leading to delays in its product releases. Two specific problems are the control of a large-scale Scrum team and the management of team commitments. To address these issues, the Scrum at Scale framework has been chosen as a solution. Before implementing Scrum at Scale, an assessment of the current Scrum maturity level at Software House XYZ is deemed necessary. The Scrum Maturity Model, adapted to the Scrum Guide 2020, is selected as the method to evaluate how effectively the company is implementing Scrum. A questionnaire comprising 81 practices was distributed to development teams, with 10 valid responses collected. Based on the assessment using the Scrum Maturity Model, the current Scrum implementation maturity at Software House XYZ is rated at level 1, Initial. A total of 61 practices are proposed for improvement in the Scrum process. Scrum at Scale can be implemented once the suggested Scrum process improvements have been made. These recommendations are structured following the framework outlined in the Scrum at Scale Guide 2022. The validation of the Scrum-at-Scale recommendations was conducted by us through interviews with representatives from Software House XYZ. From the validation results, the company expresses interest in trying to implement Scrum at Scale. However, the company agrees to enhance the existing Scrum process within the organization before fully adopting Scrum at Scale.